Criminalising Women, Silencing Victims: Human Rights and Sharia Enforcement in Aceh - Hasbi, Yusrizal; Saputra, Ferdy; Iskandar, Hadi; Rasyid, Laila Muhammad; Harun, Harun (Shariah Faculty UIN Maulana Malik Ibrahim Malang, 2025)
This study critically examines the role of Islamic law and local customs (adat) in Aceh in shaping criminalisation processes and victims’ rights, particularly focusing on the protection of women. Aceh, endowed with special autonomy within Indonesia, presents a unique legal framework that blends Islamic law (Sharia) with indigenous customary law, creating a hybrid legal environment grounded in both religious doctrine and cultural values. Although often perceived as rigid, Acehnese Islamic law incorporates a humanist ethos that prioritises community harmony and upholds women’s dignity. Using normative legal research methods, with a conceptual approach and scientific interpretation, the research evaluates the extent to which the current legal system aligns with national and international human rights standards. Specifically, it focuses on how legal norms are formulated, interpreted, and applied in cases of gender-based violence. By examining academic literature and legal analyses, this study underscores the importance of a balanced approach within Aceh’s legal framework, one that respects Islamic values and cultural traditions while strengthening the protection of women’s rights. The study’s main contribution lies in its normative critique of Aceh’s dual legal system and its recommendation to harmonise Islamic legal norms with international human rights obligations. By proposing a rights-based recalibration of the existing framework, the research offers a pathway to enhance legal protections, improve access to justice, and ensure that Islamic law functions as a means of empowerment rather than marginalisation. This review provides critical insights into the complexities of Aceh’s Islamic legal system and its broader societal implications.